2004
DOI: 10.1007/s00027-003-0669-2
|View full text |Cite
|
Sign up to set email alerts
|

Critical regions: A GIS-based model of marine productivity hotspots

Abstract: Marine productivity hotspots can be defined as areas of high chlorophyll concentration and low temperature distribution. Here we demonstrate how Geographic Information Systems (GIS) can be used to define areas of high productivity and we use fishery data to verify model results and reveal areas of potential fishery locations. We develop a GIS model based on spatial data integration between monthly satellite imagery of Advanced Very High Resolution Radiometer (AVHRR) sea surface temperature (SST) and Sea-viewin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 34 publications
1
33
0
Order By: Relevance
“…A considerable body of literature has documented that marine resources are related to productivity hotspots (e.g. Olivar 1990, Solanki et al 2001, Valavanis et al 2004). Our study demonstrated that utilized habitats for Chinook and coho salmon were generally within or in the vicinity of high chlorophyll a concentration areas.…”
Section: Choice Of Habitatmentioning
confidence: 99%
“…A considerable body of literature has documented that marine resources are related to productivity hotspots (e.g. Olivar 1990, Solanki et al 2001, Valavanis et al 2004). Our study demonstrated that utilized habitats for Chinook and coho salmon were generally within or in the vicinity of high chlorophyll a concentration areas.…”
Section: Choice Of Habitatmentioning
confidence: 99%
“…coral reefs), but in the highly productive marine areas that may extend from the shelf and further offshore. For example, productive areas such as upwelling regions account for only 0.1% of the ocean surface (Ryther 1969), yet they support up to 50%of the world's fisheries production (Valavanis et al 2004). Exploitation of these highly productive marine regions has resulted in significant declines in populations of target species (e.g.…”
Section: Highly Productive and Highly Exploitedmentioning
confidence: 99%
“…Biological hotspots are ecologically important areas characterized by high biodiversity (species richness, abundance, and biomass) and high chlorophyll concentration (Hughes et al 2002, Valavanis et al 2004, Reese & Brodeur 2006. Georges Bank exhibits both characteristics, with an nual primary productivity in the tidally mixed shoals approaching 3 times the global mean value for continental shelves (O'Reilly et al 1987).…”
Section: Introductionmentioning
confidence: 99%